Characterizing the environmental drivers of the abundance and distribution of Alopecurus myosuroides on a national scale. Issue 6 (19th February 2021) - Hicks, Helen; Lambert, James; Pywell, Richard; Hulmes, Lucy; Hulmes, Sarah; Walker, Kevin; Childs, Dylan Z; Freckleton, Robert P
Abstract: BACKGROUND: Arable weeds threaten farming and food production, impacting on productivity. Large‐scale data on weed populations are typically lacking, and changes are frequently undocumented until they reach problem levels. Managing the future spread of weeds requires that we understand the factors that influence current densities and distributions. In doing so, one of the challenges is to measure populations at a large enough scale to be able to accurately measure changes in densities and distributions. Here we analyse the density and distribution of a major weed ( Alopecurus myosuroides ) on a large scale. Our objectives were to (i) develop a methodology for rapid measurement of occurrence and abundance, (ii) test hypotheses about the roles of soils and climate variation in determining densities, and (iii) use this information to identify areas in which occurrence could increase in the future. RESULTS: Populations were mapped through England over 4 years in 4631 locations. We also analysed UK atlas data published over the past 50 years. Densities of populations show significant interannual variability, but historical data show that the species has spread. We find significant impacts of soil and rainfall on densities, which increase with the proportion of heavy soils, but decrease with increasing rainfall. Compared with independent atlas data we found that our statistical models provide good predictions of large‐scale occupancy and we provide maps of current and potential densities. CONCLUSION: Models of spread highlight the localised nature of colonisation, and this emphasises the need for management to limit dispersal. Comparisons of current, historical and potential distributions suggest sizeable habitable areas in which increases in abundance are still possible. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : A heatmap showing the current nationwide distribution of Aloecurus myosuroides in the UK (red, low density; yellow, high density).